Chemical And Physical Evaluation Of Herbal Artificial Saliva Formulations-Scoping Review - kuswandani, Faisal; Febriane Balafif, Felisha; Najmi, Nuroh; Rafisa, Anggun (Sean Institute, 2024)
Saliva plays an important role in physiological function. Alteration in saliva production results in serious health problems that affect patient oral health-related quality of life (OHRQiL). the purpose of the research was to investigate the chemical and physical evaluation of natural artificial saliva formulations. Methods, the data synthesis protocol for a rapid review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocol (PRISMA-P). Electronic databases were searched on articles published in 2004- 2024. evaluating Chemical and physical properties of herbal artificial saliva formulations in preclinical study. Results, Identification from the Science Direct and PubMed databases obtained 332 scientific articles and 3 articles met inclusion criteria. Basella alba Linn. (Ceylon Spinach mucilage) shows non-Newtonian characteristic fluid, similar to normal human saliva. It has antioxidative activity, adhesion inhibition, and non-toxic. Propolis extract and Aloe vera extract showed minimal effect on viscoelastic properties but were still in the range of normal human saliva. Dioscorea batatas (Yam tuber mucilage) viscosity shows non-Newtonian characteristic fluid and antibacterial activity by influenced the enzymatic activity of lysozyme and peroxidase. Conclusion, Chemical and physiological evaluation shows that herbal plant extract has the potential to be used as an artificial saliva constituent. It had a viscosity in the range of normal human saliva with several advantages in terms of pharmacological activity.